Faktor-Faktor yang Mempengaruhi Harga Saham Pada Perusahaan Sub Sektor Infrastruktur, Utilitas dan Transportasi - Yudhitya Putri Melati; Dedi Suselo (Universitas Islam Nahdlatul Ulama Jepara, 2022)
The purpose of this research is to analyze the impact of key components of the firm, including return on equity, debt to equity ratio interest on the the value of the book shares of construction firms. The research model covers 8 companies in the manufacturing, utilities and transport sectors listed in IDX for the period 2019-2020 using the target selection method. The panel data were analyzed using SPSS 25 and this method was integrated to obtain the best regression results. According to the study, the main factor influencing the difference in the price of a group of animals. Significant positive correlations can be found in the return on equity, the ratio of debt to equity and the book value of changes in share prices.